Effects Of Temperature On Resilient Modulus Of Dense Asphalt Mixtures Incorporating Steel Slag Subjected To Short Term Oven Ageing - Hamzah, Meor O; Teoh, C Yi (2008)
As the resources for naturally occurring aggregates diminished at an ever increasing rate, researchers are keen to utilize recycled materials in road construction in harmony with sustainable development.